Effectiveness of Biochar application on the growth of red chili plants during the vegetative stage under waterlogging - Az-Azahra, Risma Chantrika; Siaga, Erna; Herlina, Herlina; Meihana, Mei (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2024)
The riparian wetland offers potential for horticultural crop cultivation, such as chili peppers. It is important to consider cultivation techniques and the use of organic matter to improve soil properties, particularly to combat waterlogging during the rainy season. This study aimed to assess the impact of biochar application on the growth of chili peppers (Capsicum annuum L.) during the vegetative stage under waterlogging conditions. This research was conducted at the experimental land of the Agrotechnology Department, Faculty of Plant and Animal Sciences, Universitas Bina Insan from December 2022 to February 2023. This research employed a complete randomized design (RAL) factorial with two factors. The first factor involved waterlogging stress, including control (C) and waterlogging stress (W). The second factor (N) encompassed the application of biochar, namely without biochar (N0), rice husk biochar (N1) and coconut shell biochar (N2) at a dose of 200 g plant-1. The results showed that waterlogging conditions (W) and biochar application (N) showed significantly different results in shoot length, root length, number of leaves, and total dry weight of chili plants, while the interaction (WxN) showed significantly different in shoot length and root length of plants. Treatment without biochar (N0) in waterlogging conditions actually showed shoot length, root length, number of leaves and total dry weight of plants that were significantly higher than treatment coconut shell biochar (N1) and rice husk applications (N2).